Pengaruh Karakteristik Penganggaran Terhadap Kinerja Pelaksanaan Anggaran Pemerintah (Studi Pada Satuan Kerja Lingkup Wilayah Kerja KPPN Malang) - Alfons Redemptus Benedik Suluh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is aimed to analyze the influence of budgetary goal characteristics, which consists of budgeting participation, budget goal clarity, budget goal difficulty, budget feedback, and budget evaluation, to the performance of governmental budget implementation. The population in this research was financial functionaries and working units on scope of the working area of KPPN Malang. Primary data was collected using questionnaires instruments distributed to working units. This research is a quantitative’s one, and hypotheses testing used multiple regression analysis to determine the effect of the existing variables. The result of this research showed that five variables of budgetary goal characteristics, only budget goal clarity variable that had a significant influence to the performance of governmental budget implementation, while the other four variables (budgeting participation, budget goal difficulty, budget feedback, and budget evaluation) doesn’t had significant effets on the performance of governmental budget implementation. Keywords : Budgeting Participation, Budget Goal Clarity, Budget Goal Difficulty, Budget Feedback, Budget Evaluation, and Performance of Governmental Budget Implementation.